Educação antirracista e pedagogia inaciana: a experiência do Comitê de Educação para as Relações Étnico-raciais do Colégio Antônio Vieira - Paixão, Camila Portugal da (Universidade do Vale do Rio dos Sinos, 2024)
This research was conducted within the scope of the Professional Master's Program at Unisinos - Porto Alegre Campus. The study aimed to analyze the work carried out by Colégio Antônio Vieira, located in Bahia, Brazil, with regard to ethnic-racial education and its impact on institutional culture, focusing on the formative role of its Ethnic-Racial Committee (CERER). The literature review and theoretical framework of this study engage with scholars whose work contributes to advancing knowledge in several areas. These include Escrevivência (the process of writing rooted in lived experiences) as discussed by Professor Conceição Evaristo (2020); Structural Racism, as examined by Professor Silvio Almeida (2019); Antiracist Education, as explored by Professor Barbara Carine Pinheiro (2023); and Ethnic-Racial Relations, along with their structures and foundations, as presented by Frantz Fanon (2020), Nilma Lino Gomes (2012), Angela Davis (2016), Sueli Carneiro (2023), and Djamila Ribeiro (2019). In addition, the study draws on the principles of Ignatian Pedagogy, referencing documents from the Jesuit Education Network (2016). The study employed a qualitative approach, using a case study methodology to achieve its main objective, and content analysis as the technique for interpreting the data. Data collection instruments included document analysis, meetings with CERER members, and a questionnaire administered to staff and teachers at the school. The results indicate that participants recognize the need for dedicated spaces within the school to foster antiracist practices and acknowledge the existence of the CERER, though there is still a lack of active participation in its initiatives. This suggests a need to design strategies that can further engage the school community. In conclusion, this study presents its final product, which aims to contribute to the development of an antiracist education policy within the school institution. This, in turn, seeks to enhance discussions on this critical issue and foster greater involvement in the committee’s activities.
Keywords: Racismo estrutural; Educação antirracista; Pedagogia inaciana; Relações étnico-raciais; Escrevivência; Structural racism; Antiracist education; Ignatian pedagogy; Ethnic-racial relations; ACCNPQ::Ciências Humanas::Educação